Non-systemic treatment of metastatic kidney cancer: systematic review and a case report - Morkunaite, Gabija O.; Mickeviciute, Ugne; Trakymas, Mantas; Kincius, Marius; Urbonas, Vincas; Kvederas, Giedrius; Patasius, Ausvydas (Frontiers in Oncology, 2025)
Background and objectivesTo date, there is insufficient literature on the local treatment options for metastatic renal cell carcinoma (mRCC). Various options, such as metastasectomy, thermal ablation, and stereotactic body radiotherapy, have gained attention for their potential to improve survival and quality of life in selected patients’ groups. This systematic review analyzes the effectiveness of these approaches and highlights their potential to improve survival outcomes. By analyzing survival outcomes, this review aims to guide future research, thereby enhancing clinical decision-making.Materials and methodsA systematic review of studies published since 2009 was conducted, following PRISMA guidelines. Relevant articles were identified from PubMed and ScienceDirect databases, using search terms related to mRCC and non-systemic treatment. The review was not registered, and a protocol was not prepared. Additionally, a case report documenting the successful use of cryoablation in controlling metastases of kidney cancer was included to illustrate clinical relevance. ResultsThirteen studies met the inclusion criteria. Complete metastasectomy demonstrated improved overall survival (OS) and progression-free survival (PFS) compared to incomplete or no metastasectomy. Stereotactic body radiotherapy (SBRT) and other forms of radiotherapy provided effective palliation and durable disease control.ConclusionsThis systematic review highlights the potential survival benefits for mRCC patients with the use of different local treatment modalities, especially in terms of complete metastasectomy. The findings show the need for continued research to optimize local treatment strategies, along with improving the quality of life for metastatic kidney cancer patients.